Bullying victimization and nicotine and marijuana vaping among Florida adolescents. (1st August 2022) - Boccio, Cashen M.; Leal, Wanda E.; Jackson, Dylan B.
Abstract: Purpose: Previous research links bullying victimization with the use of illicit substances in adolescence. In addition, recent research has linked bullying victimization with vaping. Very limited research, however, has explored how different forms of bullying may be linked with nicotine and marijuana vaping specifically. Procedures: This study addresses this gap in the literature by utilizing logistic regression to examine the relationships between verbal, physical, and cyber bullying victimization and nicotine and marijuana vaping in a sample of Florida adolescents. Findings: Our findings reveal that all three forms of bullying victimization are linked with recent nicotine vaping, and these associations differ somewhat by youth gender. In addition, our findings indicate that cyber bullying victimization is linked with marijuana vaping. Conclusions: In conclusion, our findings suggest that bullying victimization is linked with greater odds of vaping activity in adolescents. The implications of these findings for future research and policy are discussed. Highlights: Previous research links bullying victimization with substance use. Limited research has explored the link between bullying victimization and vaping. This study examined relationships between three forms of bullying and two forms of vaping. Bullying victimization was associated with nicotine vaping. Cyberbullying victimization was associated with marijuana vaping.